Knowledge Regarding Pubertal Changes among Adolescents in Selected Schools of Jumla - K C, Reshma; Regmi, Muna (Academia Research Journal, 2025)
Adolescence (10-19 years) is a period of transition from childhood to adulthood. Rapid physical, cognitive, social, and emotional development occurs during the adolescent period. Puberty marks the development of primary and secondary sex characteristics and the attainment of the individual for reproduction is attained. To identify the associated factors related to knowledge regarding pubertal changes among adolescents in selected school of Jumla. A cross-sectional, quantitative study was conducted at two private school (Jaya Ratna Karnali Boarding School and Asia International Boarding School of Jumla). Simple random sampling technique was used to select the school and sample. Total 106 students were included in study. Structured questionnaire was developed. Data was collected by self-administered questionnaire and analyzed by using SPSS version 16. Descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (chi-square) were used to analyze the data. Majority (79.2%) of respondents had inadequate knowledge while one fifth (20.8%) had moderately adequate knowledge and none had adequate knowledge about pubertal change. A statistically significant association was found between level of knowledge with socio- demographic variables such as gender and source of information. Majority of respondents had inadequate knowledge. Therefore, there is need for health education, awareness campaign and inclusion of pubertal health content in school curricula to improve adolescents understanding to these changes.